STUDENT MOBILITY AS THE ELEMENT OF INTERNATIONALIZATION OF HIGHER EDUCATION - Mietule, Iveta; Arbidāne, Iluta; Kalniņa, Laura (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Scientific researches on the potential of export of higher education became topical more than 10 years ago, but this issue remains very topical nowadays as well, and it is essential to keep searching for solutions for the future development of this area. The aim of the paper is to analyse the general trends of student mobility in Latvia in the context of the student mobility in the world.  Hypothesis of the research - comparative research on the student mobility rates in the research period from 2011 to 2016 shows that there is higher growth of student mobility in Latvia than on the global scale. The number of mobile students in the research period is increasing both in Latvia and in the world, but the statistical survey in Latvia confirms that this growth in Latvia is more significant.